Effects of the egg incubation environment on turtle carapace development. Issue 2 (13th November 2022) - Cordero, Gerardo A.; Birk, Katie; Ruane, Sarah; Dinkelacker, Stephen A.; Janzen, Fredric J.
Abstract: Developing organisms are often exposed to fluctuating environments that destabilize tissue‐scale processes and induce abnormal phenotypes. This might be common in species that lay eggs in the external environment and with little parental care, such as many reptiles. In turtles, morphological development has provided striking examples of abnormal phenotypic patterns, though the influence of the environment remains unclear. To this end, we compared fluctuating asymmetry, as a proxy for developmental instability, in turtle hatchlings incubated in controlled laboratory and unstable natural conditions. Wild and laboratory hatchlings featured similar proportions of supernumerary scales (scutes) on the dorsal shell (carapace). Such abnormal scutes likely elevated shape asymmetry, which was highest in natural nests. Moreover, we tested the hypothesis that hot and dry environments cause abnormal scute formation by subjecting eggs to a range of hydric and thermal laboratory incubation regimes. Shape asymmetry was similar in hatchlings incubated at five constant temperatures (26–30°C). A hot (30°C) and severely Dry substrate yielded smaller hatchlings but scutes were not overtly affected. Our study suggests that changing nest environments contribute to fluctuating asymmetry in egg‐laying reptiles, while clarifying the conditions at which turtle shell development remains buffered from the external environment. Abstract : The dorsal shell (carapace) of the Blanding's turtle, Emys blandingii, was examined in hatchlings from natural versus laboratory egg incubation environments. Carapace shape asymmetry was greater in the hatchlings from natural nests.